Recent developments in acid and base-catalyzed etherification of glycerol to polyglycerols - Sivaiah, M.V.; Robles-Manuel, S.; Valange, S.; Barrault, J. (Catalysis today, 2012)
The catalyzed selective etherification of biosourced glycerol into short-chain oligomers is economically attractive and subject to increasing evolution as a result of the unique properties of polyglycerols. [Display omitted] ► Homo- and heterogeneous catalytic processes of oligomerization of glycerol have been reviewed. ► Emphasis was focused on the selective preparation of short-chain oligomers. ► Design of shaped extrudates alkaline earth-based mesoporous catalysts was also addressed. ► Highly efficient catalysts were obtained from newly developed Mg–clay materials. Commercial relevance of glycerol as a biosourced safe organic building block for valuable commodity chemicals has increased considerably with the rapid development of oleochemistry. Among the various reaction pathways for catalytic conversion of glycerol, oligomerization to polyglycerols (PGs) is one of the viable and demanding processes due to the wide field of applications of PGs in cosmetics, polymers, food-additives, antifogging film industry, pharmaceuticals, biomedicals and drug delivery systems. This short review is dedicated to the selective synthesis of polyglycerols preferentially to low molecular-weight oligomers with emphasis on the pros/cons of reported homogeneous and heterogeneous acidic and basic catalytic processes. In addition, recent advances conducted in our laboratory will be given for a selective glycerol oligomerization in the presence of powdered and shaped alkaline earth-based mesoporous catalysts and of hydrothermally synthesized layered structured materials as newly developed basic catalysts. Some critical issues and challenges regarding the rational design of solid catalysts with emphasis on their stability in hot glycerol as well as alternative reaction engineering to overcome the drawbacks stemming from batch reactions will be addressed. Selectivity to the desired fraction of short-chain oligomers for food and cosmetic applications with respect to the European Union regulations will be also introduced.